Some issues in teaching Latin for English speaking medical students - Gordiyenko, O. V.; Titiyevskaya, T. V.; Гордієнко, Олена В'ячеславівна; Тітієвська, Тетяна Василівна (Харків : Вид-во НФаУ, 2016)
Nowadays there are a lot of works dedicated to the teaching methods of different languages as a second or foreign, there are some about Latin as a classical one, but there is a lack of them if we face to the question of teaching Latin as a Language for Special Purposes, i.e. for Latin in Medicine. Teaching Latin and Basics of Medical Terminology for medical students with English medium of study has been one of the most difficult tasks at the Department of Foreign Languages of Zaporizhzhia state medical university for many years. One of the problems for students is the difficulty of adjectives and nouns coordination in Latin anatomical, clinical and pharmaceutical terminology. The thing is that English speaking medical students are mostly from India, Nigeria, Morocco and Tunisia, so their mother languages are very different.